10 Partner violence victimisation and perpetration, alcohol use, and injury among drug-using young adults seeking emergency department care: a 2-year prospective study. (19th September 2017) - Singh, Vijay; Epstein-Ngo, Quyen; Carter, Patrick; Goldstick, Jason; Salhi, Rama; Walton, Maureen; Cunningham, Rebecca
Abstract : Statement of purpose: Partner violence (PV) is associated with long-term health consequences including alcohol and drug use. This study examines severe PV victimisation and perpetration among a sample of drug-using youth seeking emergency department (ED) care, and assesses baseline correlates of PV over 2 years. Methods/approach: We consecutively sampled 14- to 24 year olds with past 6 month drug-use seeking care at an urban ED, proportionally sampling those with and without assault-related injury. Youth completed validated measures of PV, alcohol and drug use, gun possession, and community violence. We used multivariate logistic regression analyses to examine baseline predictors of severe PV over 2 years. Results: The 2 year follow-up prevalence was 264/487 (54.7%) and 209/467 (44.8%) for serious PV victimisation and perpetration, respectively. Severe PV victimisation correlates included female gender (AOR 1.93, 95% CI 1.21–3.08), mother's education (AOR 0.62, 95% CI 0.41–0.94), assault injury (AOR 2.30, 95% CI 1.10–4.84), alcohol or drug use disorder (AOR 1.57, 95% CI 1.02–2.41), gun possession (AOR 1.96, 95% CI 1.20–3.22), community violence (AOR 2.13, 95% CI 1.37–3.30), and PV victimisation (AOR 2.13, 95% CI 1.37–3.30). Severe PV perpetration correlates included female gender (AOR 2.57, 95% CI 1.59–4.16), mother's education (AOR 0.64, 95% CI 0.42–0.97), assault injury (AOR 1.70, 95% CI 1.08–2.69), community violence (AOR 1.15, 95% CI 1.07–1.22), and PV perpetration (AOR 2.02, 95% CI 1.27–3.21). Conclusions: Nearly half of past 6 month drug-using youth seeking ED care were serious PV victims or perpetrators over 2 years. Female gender, mother's education, assault injury, community violence, and baseline PV were predictive of severe PV victimisation and perpetration, while alcohol or drug use disorder and gun possession were predictive of severe PV victimisation. Significance and Contributions to Injury and Violence Prevention Science: Severe PV prevalence is high among drug-using youth seeking ED care. PV interventions should address gender, assault injury, and community violence. Mother's education was a protective factor for preventing PV.